The Future of Big Data Analytics in Supply Chain Management: Results from a Delphi Study - Roßmann, Bernhard; Canzaniello, Angelo; von der Gracht, Heiko; Hartmann, Evi (Academy of Management Proceedings, 2017)
The evermore growing amount of available data accelerated the emergence of numerous business intelligence applications that are summarised under the term Big Data Analytics (BDA). As value networks are becoming more global and complex while the amount of data is simultaneously increasing, BDA is especially relevant to the domain of supply chain management (SCM). Its application does challenge traditional institutional arrangements as well as roles that are related to the management of data. Our empirical study addresses this challenge by an application of a Delphi survey that is embedded in organisational information processing theory. For this purpose, we integrate the assessments of experts on projections up to the year 2035 to span the future of BDA in SCM. Our study suggests that BDA will improve demand forecasts, reduce safety stocks and improve the management of supplier performance. However, supply chain processes will become increasingly automated and traditional tasks of SCM are partially substituted in consequence. Consequently, the transition of the traditional role of SCM within organisations will increase the importance of human intuition, trust and strategic decision-makin